2012
DOI: 10.1111/bjc.12009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring change processes in compassion focused therapy in psychosis: Results of a feasibility randomized controlled trial

Abstract: Compassion focused therapy appears as a safe, acceptable, promising, and evolving intervention for promoting emotional recovery from psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
221
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 249 publications
(232 citation statements)
references
References 52 publications
7
221
0
4
Order By: Relevance
“…In particular, it uses relaxation, meditation and imagery exercises, typical of positive interventions, to develop feelings of kindness and compassion (Gilbert, 2009). There is a small but developing literature supporting the effectiveness of compassion focused therapy for treating mental health problems (Braehler et al, 2013;Laithwaite et al, 2009), but what has been perhaps most striking about compassion focused therapy is its popularity amongst clinical psychology therapists, many of whom have begun to incorporate the techniques outlined in it to their practice of other therapies, such as cognitive behaviour therapy (for example, see Tarrier & Johnson, 2015).…”
Section: Positive Clinical Psychology: Where Integration Is Happeningmentioning
confidence: 99%
“…In particular, it uses relaxation, meditation and imagery exercises, typical of positive interventions, to develop feelings of kindness and compassion (Gilbert, 2009). There is a small but developing literature supporting the effectiveness of compassion focused therapy for treating mental health problems (Braehler et al, 2013;Laithwaite et al, 2009), but what has been perhaps most striking about compassion focused therapy is its popularity amongst clinical psychology therapists, many of whom have begun to incorporate the techniques outlined in it to their practice of other therapies, such as cognitive behaviour therapy (for example, see Tarrier & Johnson, 2015).…”
Section: Positive Clinical Psychology: Where Integration Is Happeningmentioning
confidence: 99%
“…Focusing on the experience and development of compassion has been found to reduce depression, anxiety and self-criticism in people presenting to a community mental health team [15], in people with long term mental health problems [16], and people in a high security psychiatric setting [17]. CFT has been shown to be helpful for people with psychosis [18,19] and can significantly reduce paranoid ideation [20] and emotional difficulties for people with personality disorder difficulties [20]. Ashworth et al [21] found CFT to be a valuable addition to standard interventions in helping people with acquired brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Compassion training increases prosocial behavior (Leiberg, Klimecki, & Singer, 2011) and is helpful for people with mental health problems (e.g. Braehler, Gumley, Harper, Wallace, Norrie, & Gilbert, 2012;Gilbert & Procter, 2006;Lucre & Corten, 2012). Practices of imagining compassion for others produce changes in the frontal cortex and well-being (Lutz, Brefczynski-Lewis, Johnstone, & Davidson, 2008;Fredrickson et al, 2008;Hutcherson et al, 2008;Sprecher & Fehr, 2006).…”
mentioning
confidence: 99%